Functional transformation series and the evolutionary origin of novel forms: evidence from a remarkable termite defensive organ. Issue 2 (13th January 2016) - Kaji, Tomonari; Keiler, Jonas; Bourguignon, Thomas; Miura, Toru
SUMMARY: The origins of evolutionary novelties are often deeply puzzling. They are generally associated with new functions that were absent in ancestors. The new functional configuration should arise via intermediate stages without any loss of function or impediment to the whole organism during the transitions. Therefore, understanding of the functional configurations of transitional states can shed light on how novel forms arise. Here we infer the evolutionary origin of a highly specialized termite defensive organ "nasus" where different functions overlap in different structural configurations at intermediate evolutionary stages to ensure that each phase is functional. Soldiers of a nasutitermitine termite use reconfigured mandibular muscles to squirt a viscous secretion from a nozzle‐like head projection (the nasus). This contrasts sharply with the primitive defensive strategy where mandibles are used to bite. MicroCT observations of soldiers of Nasutitermes takasagoensis and of species with the ancestral state ( Hodotermopsis sjostedti, Embiratermes neotenicus ) revealed three different yet fully functional configurations in the transition from ancestral to novel state: (i) elevated hydrostatic pressure induced by contraction of mandibular muscles when biting gently oozes secretion from a gland; (ii) direct pressure on an enlarged gland arises from expansion of the mandibular muscles when biting; (iii) squirting in a piston‐like manner by an inflated gland enveloped by highly modified mandibular muscles. Even a structure as exotic as the nasus therefore appears to have evolved with no loss of function at any stage. Such a functional approach, holds much promise for understanding the evolutionary origin of seemingly preposterous novel forms.